UPAYA PENINGKATAN PEMAHAMAN ANAK MENGENAI BULLYING DI MADRASAH IBTIDAIYAH SWASTA TARBIYATUL FALAH AL-BAENURIYAH PAMIJAHAN BOGOR - Nurdiani, Siti Nanda; Mukri, Rusdiono; Hasanah, Tita (Primer Edukasi Journal, 2025)
According to the Survei Nasional Pengalaman Hidup Anak dan Remaja (SNPHAR) by the Kementerian Pemberdayaan Perempuan dan Perlindungan Anak (KPPPA), 2 out of 3 children aged 13-17 years in Indonesia have experienced violence. One form of violence that often occurs is bullying. This happens because of a lack of understanding about bullying. This research aims to determine the efforts made to increase students' understanding of bullying and find out how much children's understanding has increased regarding the efforts made. The research uses a quantitative approach with pre-experimental methods and the research design used is one group pre-test post-test design. This research was conducted at MI TF Al-Baenuriyah with a total of 33 students as respondents. The research results show that efforts made through media such as videos, big books and posters that discuss bullying can increase children's understanding of bullying at MI TF Al-Baenuriyah. This increase reached a value of 0.5908 or 59.08%, including the category of moderate improvement or if we use a representation table of the percentage of N-Gain results, efforts to increase children's understanding of bullying are quite effective.